The Extension of Statistical Entropy Analysis to Chemical Compounds - Helmut Rechberger; Alicja P. Sobańtka; Matthias Zessner (Entropy, 2012)
Statistical entropy analysis (SEA) quantifies the dilution and concentration of conservative substances (e.g., heavy metals) in a system. In this paper, the SEA concept is extended (eSEA) to make it applicable to systems in which the chemical speciation is of particular importance. The eSEA is applied to a simplified region used for crop farming. The extent to which the region concentrates or dilutes nitrogen compounds is expressed as the change in statistical entropy (DH). A detailed derivation for the calculation of DH is provided. The results are discussed for four variations of the crop farming system, showing that the efficiency of crop farming can be expressed by eSEA.